Remote techniques for inspection and refurbishment of nuclear plant proceedings of the international conference, organized by the British Nuclear Energy Society and co-sponsored by the European Nuclear Society, the Institution of Electrical Engineers and the Institution of Mechanical Engineers, held in Stratford-upon-Avon on 28 November-1 December 1988. (British Nuclear Energy Society, 1988)
Proceedings of an international conference held in Stratford-upon-Avon on 28 November - 1 December 1988.
Keywords: Remote handling (Radioactive substances) -- Congresses.; Nuclear power plants -- Safety measures -- Congresses.; elektronické knihy; electronic books